DIALECTIC OF ISLAMIC SOCIAL VALUES DURING THE TIME OF THE PROPHET WITH LIFE OF MODERN SOCIETY - Zahro, Fatimatus; Syafi, Muhammad Farouq Auni (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
According on Islam itself, those changes is something that must be embraced and made to an implementive factor of religion teachings. In due course, those become the problems and challenges itself to invent a precise implementation and actualization with the social changes that occurs, no matter that it’s from historical, geographic, social, politics, morals, and even ethical perspective. The purpose of these research is: 1) to examine the social aspect of Madinah Islamic civilization under the leadership of the Prophet Muhammad?. 2) To analyze the dialectics of Islamic social aspect on behalf of modern life. These research is included to qualitative research with library research type. The technique of data collecting and processing that used is library research technique. After that, the social theory that used on these research is Emille Durkheim’s social theories. The conclusion of these research is 1) Under the leadership of the Prophet Muhammad, Islam society is capable of becoming a social structure that materialize social and religion balances. 2) The social changes of modern society requires the adaptation of application and implementation from the teachings of Islamic religion.